PERAN BUNYAI DAN NAWANING DALAM MENDORONG PERKEMBANGAN PONDOK PESANTREN - Roro Fatikhin (Journal Khafi : Journal Of Islamic Studies, 2025)
This study aims to analyze the roles of Bunyai and Nawaning in promoting the development of Islamic boarding schools (pesantren) in the contemporary era. Pesantren leadership has traditionally been understood in masculine terms, positioning the Kyai as the central authority, which has often led to the marginalization of women’s contributions. This research employs a qualitative approach using a case study method conducted in several pesantren in East Lampung. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that Bunyai play a significant role as primary managers of dormitory life, female student curricula, and the strengthening of pesantren economic independence. Meanwhile, Nawaning contribute through managerial innovation, the digitalization of pesantren systems, and the dissemination of Islamic values via digital media. The synergy between Bunyai and Nawaning forms a collaborative leadership model that integrates pesantren traditions with the demands of modernity. This study emphasizes that recognition of women’s roles is a crucial factor for the sustainability and competitiveness of pesantren in the future.